2002
DOI: 10.1046/j.1365-294x.2002.01598.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonal diversity and structure within a population of the pondweed Potamogeton pectinatus foraged by Bewick's swans

Abstract: Clonal diversity within plant populations is affected by factors that influence genet (clone) survival and seed recruitment, such as resource availability, disturbance, seed dispersal mechanism, propagule predation and the age of the population. Here we studied a population of Potamogeton pectinatus, a pseudo-annual aquatic macrophyte. Within populations reproduction appears to be mainly asexually through subterranean propagules (tubers), while recruitment via seeds is believed to be relatively unimportant. RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
2
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(80 citation statements)
references
References 58 publications
7
68
2
3
Order By: Relevance
“…Such a situation is also observed in southern (KF) accessions, those that grouped together in dendrogram and PCoA 2D plot. Hangelbroek et al (2002) indicated that seeds rather than vegetative structures are responsible for gene flow within populations of P. pectinatus. This species is an important food source for many herbivorous waterfowls and water birds (Triest et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a situation is also observed in southern (KF) accessions, those that grouped together in dendrogram and PCoA 2D plot. Hangelbroek et al (2002) indicated that seeds rather than vegetative structures are responsible for gene flow within populations of P. pectinatus. This species is an important food source for many herbivorous waterfowls and water birds (Triest et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases there was a geographic pattern of diversity and also a correlation between genetic diversity and migration pathways of water birds (Mader et al 1998, Hangelbroek et al 2002. Triest and Fenart (2013) indicated a correlation between genetic structure of clones and habitat type in this species.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The host plants of M. mutica, namely pondweed Potamogeton (pectinatus) and widgeon grass Ruppia sp., are preferred food of waterfowl (Clausen et al, 2002;Green et al, 2002;Marklund & Sandsten, 2002). Dispersal by waterfowl is likely and is known to influence the genetic structure of plant populations (Mader et al, 1998;Hangelbroek et al, 2002;King et al, 2002). Thus it is likely that Macroplea (especially cocoons and eggs) are eaten by birds and survive the passage through their digestive tract.…”
Section: Population Differentiation and Mode Of Dispersalmentioning
confidence: 99%
“…Jonsson et al 1996;Auge et al 2001;Lundqvist and Andersson 2001;Persson and Gustavsson 2001;Hangelbroek et al 2002). For example, in Carex bigelowii no seed-derived plantlets have been observed in natural stands, even though the species is genotypically highly variable (Jonsson et al 1996).…”
Section: Genetic Diversity and Clonalitymentioning
confidence: 99%